Mechanism Financial Ratio Relationship in the Banking with IRF and FEVD - Supriyadi, Didit (Opción, 2019)
This paper aims to test the transmission mechanism and analyze the 6 banking ratios that exist in Indonesia and is listed on the IDX during the period of 2010-2017 financial statements. The analysis method used in this research is granger causality test, IRF and FEVD to see the mech- anism of relationship between financial ratios in banking in Indonesia. From the results of data analysis that has been done in explain that based on granger causality test, the variable ratio of banking finance averaged one-way relationship and not two-way. From the results of the IRF image that has been produced, it appears that the variable financial ratios of some are toward and away from the point or the average value of the variable banking financial ratios are in carefully. By using FEVD using table model, it is seen that the variable of banking finance ratios in the bigger is influenced by the variable itself and partly influenced by other financial ratio variables.